«Homo cogitat». The Spinozan Theory of the Conscious Mind - Travaglia, Marcos (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
This article enters the discussion of the Spinozian philosophy of mind, specifically whether it offers or not a theory about consciousness. We hold that it does and that its explication emerges through the articulation of several concepts according to a particular reading of the so-called «parallelism». We proceed as follows. First, we preliminarily characterize the Spinozan definition of mind. Then we offer an interpretation of the ontology. Lastly, we apply this reading to the mind-body relation, focusing on the physics, ideas of ideas, and conatus.